1986
DOI: 10.1002/j.2161-1912.1986.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Counseling Needs of Black High School Students: A Field‐Tested Needs Assessment Questionnaire

Abstract: The current trend of assessing students' needs in educational settings (Gill & Fruehling, 1979) includes the field of counseling (Grobe, Myatt, & Wheeler, 1978) at both the elementary (Kelly & Ferguson, 1984) and at the secondary levels (Tolbert, 1982). A needs assessment is an integral part of educational planning and evaluation. Counselors can use the results of a needs assessment to develop counseling program objectives and activities to better meet the needs of the students, while clearly and concretely es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Miller, Springer, Milford, and Williams (1986) found that Black high school students indicated vocational guidance and information as most relevant to their existing needs. These programs expose students to more career options, role models, and peers with similar interests.…”
Section: Synthesis and Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Miller, Springer, Milford, and Williams (1986) found that Black high school students indicated vocational guidance and information as most relevant to their existing needs. These programs expose students to more career options, role models, and peers with similar interests.…”
Section: Synthesis and Implicationsmentioning
confidence: 98%
“…Such programs may be implemented more widely to facilitate the career development of ethnic minorities. Miller, Springer, Milford, and Williams (1986) found that Black high school students indicated vocational guidance and information as most relevant to their existing needs. Lucas (1993) also found that Black college freshmen were particularly concerned with a lack of occupational information, career decision-making skills, and racial, sex, or other types of discrimination.…”
Section: Synthesis and Implicationsmentioning
confidence: 98%
“….á≤ãdGh ìÉéaedG º¡jód RõY É ‡ »ÁOÉcC 'G º¡FGOC Gh º¡JGQób ÚH ΩΩÉé°ùfG ∑Éaeg ¿Éc áfƒµμe ájƒfÉãdG á∏MôŸG áÑ∏W øe áae«Y ≈⋲∏Y (Miller, 1986) ô∏∏«e ÉgGôLC G á°SGQO 'h áÑ∏£dG äÉLÉM ¿C G É¡éFÉàf äQÉ°TC G ,᫵μjôeC 'G ÉfÉjõjƒd áj'h øe áÑdÉWh ÉÑdÉW (7458) øe (2) ºbQ ∫hó÷G ô°ûY ≈⋲∏YC ' ᫪gC 'G iƒà°ùeh ájQÉ«©ŸG äÉaGôëf'Gh á«HÉ°ù◊G äÉ£°SƒàŸG á°SGQódG áae«Y OGôaC G äGôjó≤J Ö°ùM äÉLÉM…”
unclassified
“…«∏°S OÉ©°S .O ,øeÉ° †dG Qòaee.O Ȫ°ùjO 4 ΩΩƒ∏Z á°SGQO ™e ≥Øàj Qƒ©°ûdGh ôJƒàdGh ≥∏≤dG É¡ªgC G á«°ùØf äÓµμ°ûe øe ¿ƒfÉ©j áae«©dG OGôaC G øe % 28 ¿C G âjƒµμdG ¢ †bÉaeàj Gògh .á«°ùØaedGh á«ÁOÉcC 'G äÉLÉ◊G ó©H á«ae¡ŸG äÉLÉ◊G Ö«JôJ AÉL óbh . ∫ɪgE 'ÉH äÉLÉM ¿C G ¬à°SGQO èFÉàf äô¡XC G å«M (Miller, 1986). ô∏∏e ÉgGôLC G »àdG á°SGQódG ™e πbC 'G äÉLÉ◊G âfÉch äÉeƒ∏©ŸG ≈⋲∏Y ∫ƒ°ü◊Gh ,»ae¡ŸG ¬«LƒàdG âfÉc ᫪gG ÌcC 'G áÑ∏£dGäGÒ¨àe ábÓ©H ≥∏©àj ɪ«ah .á«YɪàL'Gh á«°üî°ûdG äÉLÉ◊ÉH á≤∏©àŸG äÉLÉ◊G »g ᫪gC G äÉ«∏µμdG áÑ∏W äÉLÉM ¿C G á°SGQódG èFÉàf äô¡XC G ó≤a ,¢ùae÷Gh »°SGQódG iƒà°ùŸGh ,á«∏µμdG OGƒŸG ¿C G ∂dP Ò°ùØJ øµμÁh .ádGO ¥hôØHh ᫪∏©dG äÉ«∏µμdG áÑ∏W äÉLÉM øe ÈcC G á«fÉ°ùfE 'G äÉ«∏µμdG ' øjôNB 'G áÑ∏£dG É¡°SQój »àdG ∂∏J øe ÌcC G á«fÉ°ùfE 'G äÉ«∏µμdG áÑ∏W É¡°SQój »àdG º¡fE Gh á°UÉN .…”
unclassified